Peningkatan Kesadaran Masyarakat Dalam Pengelolaan Sampah Rumah Tangga Melalui Media Edukasi Di Lingkungan Permukiman - Syaputra, Dimas; Vianus, Antoni Okta; Pebrianti, Nedya Rike; Rosminia, Peti; Fratenza, Wahyuda; Herlina, Yuni; Hermana, M. Arafat; Mujiono, Mujiono (LPPJPHKI Universitas Dehasen Bengkulu, 2026)
Household waste management in residential areas remains a significant challenge due to the low level of public awareness regarding proper waste disposal practices. This community service activity aimed to increase public awareness of household waste management through the use of educational media in residential environments. The methods employed included environmental observation, coordination with local community leaders, development of simple and persuasive educational messages, installation of educational media at strategic locations, and brief socialization activities for residents. The results indicated that the educational media helped raise residents’ awareness of environmental cleanliness and served as a reminder to avoid improper waste disposal, particularly in drainage channels and along residential roads. The community showed positive responses and began to demonstrate improved attitudes toward maintaining cleanliness around their homes and public facilities. These findings suggest that well-designed educational media, placed in frequently accessed areas, can effectively encourage behavioral change in household waste management. Program sustainability requires continued support from community leaders and active participation from residents through monitoring and routine environmental cleaning activities